Safety and Pharmacokinetic Study of Fidaxomicin in Children With Clostridium difficile–Associated Diarrhea: A Phase 2a Multicenter Clinical Trial. (31st May 2017) - O'Gorman, Molly A; Michaels, Marian G; Kaplan, Sheldon L; Otley, Anthony; Kociolek, Larry K; Hoffenberg, Edward J; Kim, Kwang Sik; Nachman, Sharon; Pfefferkorn, Marian D; Sentongo, Timothy; Sullivan, Janice E; Sears, Pamela
Abstract : Fidaxomicin was well tolerated in a pediatric population (aged 11 months to 17 years, n = 38) with Clostridium difficile– associated diarrhea. The pharmacokinetic profile was similar to that reported for adults (high fecal concentrations, low plasma concentrations), and the clinical response rate was high. Abstract: Background: Fidaxomicin is an approved therapy for Clostridium difficile– associated diarrhea (CDAD) in adults. The safety of fidaxomicin in children has not been reported. Methods: In this study (ClinicalTrials.gov identifier NCT01591863), pediatric patients with CDAD received twice-daily oral fidaxomicin at a dose of 16 mg/kg per day (up to 200 mg) for 10 days in an open-label study. Plasma and fecal samples were collected for pharmacokinetic assessments. The primary outcome measure was safety, which was assessed by adverse-event (AE), laboratory, and physical examination/vital-sign monitoring. Efficacy was determined through early and sustained clinical response rates (clinical response without recurrence of CDAD). Results: The study enrolled 40 patients (11 months to 17 years of age), many with underlying comorbidity, including neoplasm (23.7%), gastrointestinal disorder (78.9%), and history of CDAD (60.5%). Plasma fidaxomicin and OP-1118 (the major fidaxomicin metabolite) 3- to 5-hour postdose concentrations were 0.6 to 87.4 and 2.4 to 882.0 ng/mL, respectively, and no age-related trends were seen. Fecal fidaxomicin concentrations within 24 hours of the last dose averaged 3228 µg/g, and higher concentrations and greater variability in the youngest age group were found. AEs were reported in 73.7% of the patients; most of them were mild (44.7%) to moderate (21.1%) and were considered treatment-related in 15.8% of the patients. Overall, the early clinical response rate was 92.1%. The rate of sustained clinical response (clinical response without recurrence through 28 days after treatment) was 65.8% overall. Conclusions: Fidaxomicin was well tolerated in children with CDAD and has a pharmacokinetic profile in children similar to that in adults. The clinical response rate was high.